Production Technology and Damping Properties of Aerated Polymer Coatings - V. K. Sheleg; Ma Min; M. A. Belotserkovsky (Наука и техника)
The process of obtaining aerated (filled with air bubbles) polymer coatings has been developed and investigated by the method of flame spraying with an assessment of their ability to damp vibrations. A technology for the controlled formation of aerated polymer coatings has been developed while using the capabilities of the ОИМ (OIM) 050 polymer thermal atomizer design which consists in providing a concurrent air flow between the flame torch and the jet of powder material. The experiments have been carried out with such thermoplastic polymers as polyethylene terephthalate, high pressure polyethylene, ultra high molecular weight polyethylene, polyamide. It has been found that the aeration coefficient grows almost in direct proportion with an increase in the amount of air in the concurrent flow for all investigated polymer coatings. It is noted that the aeration process is influenced by the rheological properties of liquid polymers, or rather, the value of the polymer melt flow rate. The limiting values of air in the concurrent flow have been determined, which make it possible not to reduce the adhesion of polymer coatings to steel substrates by less than 6 MPa and not to decrease their hardness by more than 25–30 %. Studies of the damping properties of samples with polymer coatings have been carried out on a stand, the kinematic diagram of which is based on loading the free end of a cantilever sample, abrupt removal of the load and registration of free damped oscillations by an induction-type contactless sensor connected to a computer. It is shown that the use of aeration when forming noise-absorbing coatings on steel samples can increase their logarithmic damping decrement by 18–26 %.